Continuous Chelation Concept in Endodontics - Ayat H Adham; Ahmed H Ali; Francesco Mannocci (College of Dentistry/ University of Baghdad, 2022)
Background:Continuous chelation can be defined as the concept of using a single mix of a weak chelator with NaOCL throughout the entire root canal preparation procedure without causing a reduction in the antimicrobial and proteolytic activity of NaOCL. Etidronic acid, also known as "1-Hydroxyethylidene-1, 1-Bisphosphonate" HEBP, or HEDP, is a soft biocompatible chelator utilized in direct combination with sodium hypochlorite to form an all-in-one deproteinizing, disinfecting, and chelating solution. It's the only chelator available as a certified commercial product, "Dual Rinse HEDP," approved for endodontic usage. This review aims to analyze and bring up-to-date data about the continuous chelation protocol using a combination of HEDP with sodium hypochlorite in endodontic irrigation. Data: only papers that were published electronically were searched within the review. Sources: "Google Scholar"," PubMed" websites were used for searching data by using the following keywords: : Bisphosphonates, Continuous chelation, Dual rinse HEDP, Etidronate, HEBP. The most relevant papers related to the topic were chosen, specifically the original articles and clinical studies, including only English-language articles from 2005 to September 2022. Conclusion:Combining a weak chelator with NaOCL solution, a single irrigation solution mixture with soft tissue dissolving ability and antibacterial properties with chelating capability can be created, which can be considered a good alternative to the conventional irrigation protocol (sequential irrigation) with NaOCL followed by using a strong chelator such as EDTA. The obvious benefit is that only one solution is required for root canal  cleansing and decontamination, also decreasing the time for irrigation and providing better conditioning of root canal walls for root-filling materials